2019
DOI: 10.1111/1467-9566.12842
|View full text |Cite
|
Sign up to set email alerts
|

Health information work and the enactment of care in couples and families affected by Multiple Sclerosis

Abstract: Given the considerable emphasis placed on informed choice, the management of health information has become an increasingly important part of living with chronic illness. This paper explores the intra-familial dynamics of managing health information in the context of chronic illness. Drawing on 77 interviews with people affected by Multiple Sclerosis in the UK (patients, partners, family members and close friends), we show how families develop their own idiosyncratic information practices, including the careful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 60 publications
(62 reference statements)
1
17
0
Order By: Relevance
“…This study is also consistent with prior research in demonstrating that people with MS obtain information about their disease and prognosis from a number of sources, including clinicians and healthcare providers, family and friends, other people with MS, the NMSS and other MS advocacy and information organizations, support groups, health and popular journals, social media, and various Internet-based sources (Bishop et al, 2009;Calabro et al, 2014;Colombo et al, 2016;Fernandez, 2013;Mazanderani et al, 2019;Marrie et al, 2019;Morgan-Followell, Nicholas, & Weisleder, 2014;Synnot et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study is also consistent with prior research in demonstrating that people with MS obtain information about their disease and prognosis from a number of sources, including clinicians and healthcare providers, family and friends, other people with MS, the NMSS and other MS advocacy and information organizations, support groups, health and popular journals, social media, and various Internet-based sources (Bishop et al, 2009;Calabro et al, 2014;Colombo et al, 2016;Fernandez, 2013;Mazanderani et al, 2019;Marrie et al, 2019;Morgan-Followell, Nicholas, & Weisleder, 2014;Synnot et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…The types of information people seek about their MS are predictably diverse and can range from specific questions about the disease and its treatment to broad questions about issues of supports for healthy living with MS (Mazanderani et al, 2019). Further diversifying and personalizing people's MS and their information-seeking/treatment preferences are the methods through which they seek and consume information, the information they prioritize, and the information they need more of or feel they are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…However, Mazanderani et al showed that when one member of a couple (eg the patient) avoided or ignored information, the other usually compensated by taking on the responsibility of managing information. Therefore, understanding the disease is viewed as a shared rather than individual concern …”
Section: Discussionmentioning
confidence: 99%
“…For couples with one individual having multiple sclerosis, shared interviews highlighted how roles and responsibilities for the information search can change over time, often depending on symptoms. Usually, only one family member, the patient or their partner, takes this responsibility . For couples with one individual having cardiovascular disease, some assessed the illness as a transformative experience in their lives, bringing them closer together.…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the evolution of fans' involvement as dedicated members of a music community, observation and inquiry involved both an emic and an etic understanding of the phenomenon (Crotty, 2010), which led to the themes used in analysis (Nowell et al, 2017). The Results and Discussion sections were combined to link the findings clearly across themes and establish the interconnectedness of the narrative in displaying the evolution of social meanings in this context (e.g., Mazanderani et al, 2019).…”
Section: Methodsmentioning
confidence: 99%